HSV-1 as a Model for Emerging Gene Delivery Vehicles. (27th May 2013) - Lim, Filip
Abstract : The majority of viral vectors currently used possess modest cargo capability (up to 40 kb) being based on retroviruses, lentiviruses, adenoviruses, and adenoassociated viruses. These vectors have made the most rapid transition from laboratory to clinic because their small genomes have simplified their characterization and modification. However, there is now an increasing need both in research and therapy to complement this repertoire with larger capacity vectors able to deliver multiple transgenes or to encode complex regulatory regions, constructs which can easily span more than 100 kb. Herpes Simplex Virus Type I (HSV-1) is a well-characterized human virus which is able to package about 150 kb of DNA, and several vector systems are currently in development for gene transfer applications, particularly in neurons where other systems have low efficiency. However, to reach the same level of versatility and ease of use as that of smaller genome viral vectors, simple systems for high-titer production must be developed. This paper reviews the major HSV-1 vector systems and analyses the common elements which may be most important to manipulate to achieve this goal.